2000
DOI: 10.1016/s0008-6363(99)00343-0
|View full text |Cite
|
Sign up to set email alerts
|

Participation of prostaglandin E2 in the endothelial protective effect of ischaemic preconditioning in isolated rat heart

Abstract: These results suggest that IPC affords protection to endothelial function in coronary arteries of the rat partially via the release of PGE2. Under our experimental conditions, the protective effect of PGE2 is mediated by PKC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…On the other hand, expression of PGH synthase gene leading to increased levels of prostacyclin and PGE 2 markedly attenuated endotoxin-induced pulmonary edema and release of thromboxane B2 [49]. Protective effects of PGE 2 on the endothelial function have been reported in the ischemia-reperfusion model using isolated rat hearts [50]. Our studies demonstrate barrier-protective effects of PGE 2 and prostacyclin in human pulmonary EC and show significant protective effect of prostacyclin in the murine model of ventilator-induced lung injury.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, expression of PGH synthase gene leading to increased levels of prostacyclin and PGE 2 markedly attenuated endotoxin-induced pulmonary edema and release of thromboxane B2 [49]. Protective effects of PGE 2 on the endothelial function have been reported in the ischemia-reperfusion model using isolated rat hearts [50]. Our studies demonstrate barrier-protective effects of PGE 2 and prostacyclin in human pulmonary EC and show significant protective effect of prostacyclin in the murine model of ventilator-induced lung injury.…”
Section: Discussionmentioning
confidence: 98%
“…In the past, we have used the present experimental model extensively to study the mechanisms involved in the endothelial protective effect of preconditioning [8][9][10]27]. The coronary flow rate and duration of ischemia were selected in the beginning to inflict a selective endothelial dysfunction, which was confirmed by the blunted coronary vasodilatation to the endothelium-dependent dilator, 5-HT [28], contrasting with the full response to the endothelium-independent vasodilator SNP.…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, cannabinoids increase the activity of protein kinase C (PKC) [40], a key player in the endothelial protective effect of preconditioning [10,12,41]. Randall et al reported that the anandamide-induced coronary relaxation in isolated rat hearts is blocked by a calcium-dependent potassium-channel blocker [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, I believe, we have an excellent example of the principle proverbially illustrated by the strikingly disparate interpretations of the true nature of an elephant by a group of blind men, each one based upon the limited palpation of a different appendage thereof. Similarly, the somewhat remarkable salutary effects of ischemic preconditioning have been variously attributed to arachidonic acid metabolism (prostaglandins/leukotrienes), 18,19 acidosis, 20 calcium fluxes, 21 reactive oxygen species ("free radicals"), 4,[22][23][24][25] including the currently fashionable nitric oxide free radical, 26 the synthesis of antioxidant enzymes, 27 heat shock protein expression, 28,29 the PARS pathway, 30 apoptosis, 31 purine (adenosine) signaling, 32 kinins, 33,34 glutamate receptors, endothelial adhesion molecule expression, 5,35,36 and a host of intracellular signalling pathways, including tumor necrosis factor, 37 protein kinase C, 38 G-proteins, ceramide, 39 and innumerable others. Indeed, each of the above cited studies does suggest the association of one or more of the above mechanisms with the clinically relevant beneficial effects of ischemic preconditioning.…”
mentioning
confidence: 99%